PELUANG DAN PENGEMBANGAN BISNIS SOFTWARE HUMAN RESOURCE INFORMATION SYSTEM DI ERA REVOLUSI INDUSTRI 4.0 - Susanto, Primadi Candra; Naik Henokh Parmenas (P3M Trisakti School of Insurance (TSI), 2021)
The purpose of this study is to see how effective the use of human resource information system software in companies is, one of the benefits of which is to take advantage of various administrative processes and also work in the personnel and human resources department. For example, this human resource information system software will make it easier for companies to collect curriculum vitae. This research method is a literature study by comparing several existing theories, previous research and interviews with several sources. The findings of human error or mistakes that are usually made when administrative work is done manually can be reduced by using human resource information system software, which can be part of the solution to reduce the high level of mental workload by upgrading the system at work. All personnel and human resource work this can be done in one platform that will make it easier for employees and also the company. From this research, it can be said that the human resource information system software is a system in which there are various features to assist the company's human resource performance process such as attendance, salary, reimbursement, leave application, and others. Human resource information system software is used as a form of investment to manage human resources in the company.